Amphoraceras rothschildi and A. jordani sp. n.: two sibling species (Lepidoptera: Erebidae) - Zilli, Alberto (Fragmenta entomologica, 2018)
One new species of Amphoraceras which has so far remained unrecognised and intermingled within A. rothschildi is described as A. jordani sp. n. Both species are endemic to New Guinea, where they even happen to locally coexist and overlap phenologically. Main diagnostic features between the two taxa occur in the development of the unusual amphora-shaped structure present on male antenna, which is herewith detailed morphologically, aspects of the habitus and features of the genitalia.